The Benefits of Cultural Intelligence in Reducing Job Stress of Flight Attendants: Evidence from International Flights of Vietnamese Airlines - Bui Nhat , Vuong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The aim of this study is to examine the contribution of cultural intelligence (CQ) to reducing job stress (JS). In addition, the mediating role of intercultural communication competence (ICC) and service attentiveness (SA) and the moderating role of ethnocentrism (ETH) are also considered. Survey data collected from 132 flight attendants serving international flights of Vietnamese airlines (Vietjet Air, Pacific Airlines, Vietravel Airlines, Bamboo Airways, and Vietnam Airlines) was analyzed. Results from partial least squares structural equation modeling (PLS-SEM) showed that cultural intelligence helps reduce job stress; this relationship is partly mediated through ICC and SA. Furthermore, this study also found that flight attendants with high ethnocentrism dampened the positive association between CQ and ICC. This finding also implied that airlines have appropriate policies to develop the cultural intelligence of flight attendants to reduce stress levels at work.